GENDER TRANSFORMATION-BASED DOMESTIC VIOLENCE VICTIM EMPOWERMENT MODEL IN NORTH ACEH DISTRICT - Kurniawan, Rudi; Aruni , Fidhia; Adawiyah , Rabiatul; Safrida; Kamaly, Nurul (Natapraja, 2025)
The North Aceh Regency ranks second in domestic violence (DV) cases in the Aceh Province, following the city of Banda Aceh. This study examines a Gender Transformation-based Empowerment Model for Victims of Domestic Violence, aiming to analyze and describe an economic empowerment model that enables victims to enhance their welfare and independence. Employing qualitative research methods through a phenomenological approach and literature review, data were collected via interviews with representatives from the North Aceh Office of Social Affairs, Women’s Empowerment and Child Protection, local government stakeholders, and victims of domestic violence. The findings reveal that economic factors are the predominant causes of domestic violence in North Aceh. Government assistance in the region remains largely focused on legal and psychological support, while economic empowerment initiatives are still limited in scope. The implementation of a Gender Transformation-based economic empowerment model offers victims access to economic resources and helps to challenge prevailing societal norms and power structures that marginalize women. This approach promotes gender equality by enabling victims to participate more actively in economic and social spheres, including access to education, vocational training, and employment opportunities.